PELAKSANAAN KETERAMPILAN TATA RIAS PADA ANAK TUNARUNGU DI SLB N KOTA SUNGAI PENUH - Dela Viska Oktaviantari (Jurnal Penelitian Pendidikan Khusus, 2014)
This research is motivated when the researcher doing some preliminary study in SLB N Sungai Penuh. This school has much concerns on cosmetology skills applied for deaf children at SMPLB and SMALB. This research becomes more interesting since the researcher has got more informations about it. The children have generated many achievements on cosmetology since this skill being applied at school. This phenomenon raises the interest to do in depth-research about the implementation of cosmetology skills on deaf children in SLB N Sungai Penuh.